Persepsi Hubungan dengan Orangtua terhadap Internalizing dan Externalizing Problems Remaja: Is the Perception of Relationship with Parents Related to Internalizing and Externalizing Problems in Adolescents? - Nandy Agustin Syakarofath; Aninditha Ramadhanti Sudiana (Jurnal Ilmu Keluarga dan Konsumen, 2025)
Adolescence is a transitional period toward adulthood, during which individuals are vulnerable to emotional issues, peer problems, and behavioral challenges associated with internalizing and externalizing problems. One of the risk and protective factors in this phase is how adolescents perceive their relationship with both parents, whether in a positive or negative light. This study aims to examine the role of perceived parent–child relationships in internalizing and externalizing problems. A quantitative research design was employed, with a sample of 144 adolescents aged 11–17 years, selected through accidental sampling. The results of a simple regression analysis showed that adolescents' perception of their relationship with their mother significantly influenced both internalizing and externalizing problems. However, the perception of the relationship with the father did not show a significant influence on either type of problem. The findings suggest that the maternal figure plays a crucial role in strengthening emotional bonds through appreciation, support, and protection, enabling adolescents to feel secure and motivated to show filial devotion. As children mature, they tend to reciprocate the affection they have received. Moreover, a mother’s protection can ease the burden on adolescents in assuming parental roles. A mother’s happiness is also essential, as it directly impacts the well-being of the child.